COMBINING SGLT2 INHIBITORS AND FINERENONE IN CARDIOVASCULAR-KIDNEY-METABOLIC (CKM) SYNDROME: A CLINICAL UPDATE - Przemysław Krukowski; Zuzanna Gąsior; Maria Grabowska; Michał Stermach; Michał Maciejowski; Mateusz Zdaniewicz; Zuzanna Lecyk; Agata Leszek; Kacper Ćwiek; Adrianna Przedborska (Archiv Euromedica, 2026)
Background Patients with chronic kidney disease (CKD), particularly those with type 2 diabetes (T2D) and albuminuria, remain at substantial risk of kidney disease progression and cardiovascular complications despite established therapy. SGLT2 inhibitors and finerenone act through distinct and potentially complementary mechanisms. Aims To evaluate the mechanisms, clinical effects, and safety of combined SGLT2 inhibitor and finerenone therapy in patients with CKD, particularly those with T2D and albuminuria, and to consider these findings within the broader cardiovascular kidney metabolic (CKM) framework. Materials and Methods A narrative review was conducted using PubMed, Scopus, and Web of Science. Publications available up to June 2026 were considered. The search focused on SGLT2 inhibitors, finerenone, CKD, heart failure, eGFR, albuminuria, and cardiorenal syndrome. After removal of duplicates and application of eligibility criteria, 44 publications were retained for qualitative synthesis. Results SGLT2 inhibitors primarily affect glomerular hemodynamics, natriuresis, and metabolic pathways, whereas finerenone modulates mineralocorticoid receptor mediated inflammatory and fibrotic pathways. The CONFIDENCE trial showed that simultaneous initiation of finerenone and empagliflozin produced a greater reduction in UACR than either monotherapy over 180 days. Meta analytic and observational data suggest potential additional benefits for MAKE, ESRD, some cardiovascular outcomes, and all cause mortality, although these findings vary according to comparator and study design. Hyperkalemia risk may be lower than with finerenone monotherapy but remains higher than with SGLT2 inhibitor monotherapy in some comparisons. An early decline in eGFR was observed, whereas acute kidney injury and symptomatic hypotension were uncommon. Conclusions Combined SGLT2 inhibitor and finerenone therapy is a promising option for carefully selected patients with CKD, T2D, and albuminuria. The strongest randomized evidence concerns reduction in albuminuria, whereas evidence for long term kidney and cardiovascular outcomes and mortality remains limited. Hyperkalemia risk is not eliminated, and regular monitoring of serum potassium and kidney function remains necessary. Extrapolation to the broader CKM population and to patients with heart failure requires further investigation.